V. A. Negovsky's Philosophical Views - G. G. Poroshenko; I. O. Zaks (Общая реаниматология, 2008)
The authors consider V. A. Negovsky's philosophical views of the processes of human dying and reanimation, which are presented in his philosophical articles. Particular emphasis is laid to the definition of death, the separation of the concepts of clinical and biological deaths, to the introduction of the concept of social death and the problem «life after death».